The Variation of University Physics Students' Experience of Plus and Minus Signs in 1D Vector-kinematics Revisited. Issue 1 (2nd January 2022) - Eriksson, Moa; Euler, Elias; Linder, Cedric; Eriksson, Urban; Govender, Nadaraj
Abstract : This article revisits and expands upon a previous phenomenographic study characterising the qualitatively different ways in which South African undergraduate physics students may experience the use of +/– signs in one-dimensional kinematics (1DK). We find the original categorisation as applicable for interpreting Swedish university-level students' responses to 1DK questions. However, by way of a typology of potential learning outcomes associated with +/– signs in 1DK, our review of the topic reveals that the original study's treatment misses the implications of +/– signs related to time rate of change and graphical shape. We also add to the description of students' experience of +/– signs in 1DK by incorporating ideas from the Variation Theory of Learning and by focusing on some of the aspects of +/– signs in 1DK that were underemphasized in the original study. Our analysis thus provides a template for physics educators to support students' conceptual understanding of sign conventions in vector kinematics.